2020
DOI: 10.1039/d0cc04462h
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective [3+2] annulation of isatin-derived MBH-carbonates and 3-nitroindoles enabled by a bifunctional DMAP-thiourea

Abstract: Highly enantioselective [3+2] annulation of isatin-derived MBH-carbonates and 3-nitroindoles was achieved by a chiral DMAP-thiourea bifunctional catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…83 In 2020, to solve the issue of controlling the enantioselectivity of the reaction, Tian, Lin, Ge, Gao and coworkers utilized a chiral DMAP-thiourea C42 as a bifunctional catalyst to enable a highly enantioselective CADA [3 + 2] annulation of 3-nitroindoles 176 with MBH carbonates 186, which synthesized a series of cyclopentaindoline-based spirooxindoles 187 in high yields and excellent stereoselectivities (Scheme 44b). 84 Furthermore, preliminary biological evaluation discovered that product 187b displayed promising inhibition activity against pancreatic lipase. Scheme 42 Organo-CADA [3 + 2] cycloaddition of 3-nitroindoles with allenoates by Zhang's group.…”
Section: Organo-cada Reactions Of 3-nitroindolesmentioning
confidence: 99%
See 1 more Smart Citation
“…83 In 2020, to solve the issue of controlling the enantioselectivity of the reaction, Tian, Lin, Ge, Gao and coworkers utilized a chiral DMAP-thiourea C42 as a bifunctional catalyst to enable a highly enantioselective CADA [3 + 2] annulation of 3-nitroindoles 176 with MBH carbonates 186, which synthesized a series of cyclopentaindoline-based spirooxindoles 187 in high yields and excellent stereoselectivities (Scheme 44b). 84 Furthermore, preliminary biological evaluation discovered that product 187b displayed promising inhibition activity against pancreatic lipase. Scheme 42 Organo-CADA [3 + 2] cycloaddition of 3-nitroindoles with allenoates by Zhang's group.…”
Section: Organo-cada Reactions Of 3-nitroindolesmentioning
confidence: 99%
“…Scheme 44 Organo-CADA [3 + 2] annulation of 3-nitroindoles with MBH carbonates. 83,84 Scheme 45 Organo-CADA spirocyclization of C3-functionalized indoles via cascade catalysis by You and coworkers. 85 Finally, an intramolecular dearomative cyclization occurred, which realized the spirocyclization and afforded products 195.…”
Section: Organo-cada Reactions Of Other Substituted Indolesmentioning
confidence: 99%
“…recently showed that a related enantioselective (3+2) annulation reaction could be performed on electrophilic 3-nitroindoles 1, in the presence of a bifunctional DMAPthiourea organocatalyst 56. 37 Spirooxindoles 57, bearing a cyclopentannulated indoline and three consecutive stereocenters, were thus obtained in high yields and enantioselectivities (Scheme 22). Scheme 22: (3+2) annulation between 3-nitroindoles 1 and isatin-derived MBH carbonate 55 in the presence of the bifunctional organocatalyst 56.…”
Section: Scheme 15mentioning
confidence: 99%
“…Scheme 21: (3+2) Formal cycloadditions in the presence of -functionalized allenoates 53.Starting from a different substrate that is an isatin-derived Morita-Baylis-Hillman (MBH) carbonate 55, Gao, Ge, Tian and coll. recently showed that a related enantioselective (3+2) annulation reaction could be performed on electrophilic 3-nitroindoles 1, in the presence of a bifunctional DMAPthiourea organocatalyst 56 37. Spirooxindoles 57, bearing a cyclopentannulated indoline and three consecutive stereocenters, were thus obtained in high yields and enantioselectivities (Scheme 22).…”
mentioning
confidence: 99%
“… 2 Synthetic efforts involving these polycyclic systems focus on the development of the dearomatization of indoles 3 either by the electrophilic activation of indole substrates bearing nucleophilic sites ( Scheme 1 a) 4 or by dearomative cycloadditions ( Scheme 1 b). 5 The de novo synthesis of polycyclic indolines, chemical transformations of sophisticated aniline-derived substrates, despite being interesting, required expensive transition metal catalysts. 6 Consequently, we were interested in the development of a novel cascade reaction to produce the polycyclic indolines from easily available aniline-derived substrate A with Tf 2 C=CH 2 (Tf = SO 2 CF 3 ), which exhibits outstanding high electrophilicity ( Scheme 1 c).…”
mentioning
confidence: 99%